2014
DOI: 10.9745/ghsp-d-13-00164
|View full text |Cite
|
Sign up to set email alerts
|

The imperative for health promotion in universal health coverage

Abstract: Health promotion and disease prevention have huge impact on health, yet given low priority, risk being overlooked in universal health coverage efforts. To effectively prioritize promotion and prevention, strong cadres of personnel are needed with expertise in legislation and health policy, social and behavior change communication, prevention and community health, health journalism, environmental health, and multisectoral health promotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…According to Springer et al, HEPs play a role in building skills, knowledge, and positive attitudes of individuals relating to health (Springer, Evans, Ortuño, Salvo, & Varela Arevalo, 2017). This conclusion is similar to that of a study conducted by Coe and de Beyer, who argue that HEPs provide individuals with more information concerning mental, physical, emotional, and social health, besides playing a key role in motivating individuals to not only improve, but also maintain their health, prevent disease, and reduce risky behaviors (Coe & de Beyer, 2014).…”
Section: Health Education Programs To Improve Men's Engagement In Heasupporting
confidence: 55%
“…According to Springer et al, HEPs play a role in building skills, knowledge, and positive attitudes of individuals relating to health (Springer, Evans, Ortuño, Salvo, & Varela Arevalo, 2017). This conclusion is similar to that of a study conducted by Coe and de Beyer, who argue that HEPs provide individuals with more information concerning mental, physical, emotional, and social health, besides playing a key role in motivating individuals to not only improve, but also maintain their health, prevent disease, and reduce risky behaviors (Coe & de Beyer, 2014).…”
Section: Health Education Programs To Improve Men's Engagement In Heasupporting
confidence: 55%
“…In the long term, with the evidence from this research, Chinese policy makers and care providers should consider the effectiveness of preventive care to increase the awareness of older adults' health condition. PCU also should be promoted as a type of disease prevention and personal health investment …”
Section: Discussionmentioning
confidence: 56%
“…PCU also should be promoted as a type of disease prevention and personal health investment. 15,39 In this study, we treated PCU as a process factor, suggested by the Donabedian's framework for health care quality. 22,40 With a valid theoretical framework, it supported the authors of this research to justify the significance of the topic 41 and provide more practical implications.…”
Section: Discussionmentioning
confidence: 99%
“…Then, a study by Rahmawati 15 in 2007 stated that mothers with young children exhibited better improvements on knowledge and behavior after being taught using audiovisual media than conventional media (e.g., modules). Another study by Sweeney 16 in 2012 also stated that technology presents an ideal means for healthcare Centrees to improve public health status. Thus, healthcare officers should be familiar in using technology to promote health and better disperse health information.…”
Section: Discussionmentioning
confidence: 99%